goMiletika v kievskoj bogoslovskoj tradicii: obščeteoretičeskie podchody i ich praktičeskaja realizacija (XVII – načalo XIX vv.) = Homiletics in the Kyivan Theological Tradition since the 18th till the beginning of the 20th Century: General Theory and Particular Implications - Bureha, Vladimir (Bogoslovskie razmyšlenija, 2018)
Article is devoted to the review of history of formation homiletics as sciences in the Kiev theological tradition. On the basis of the analysis of the first domestic work under the theory of the sermon, made by Ioanniky Galjatovsky, process of influence of the Catholic baroque sermon on origin homiletics in Kiev in XVII century is shown. There is also a homiletic views of archbishop Feofan Prokopovich analysis, aspiring to reform the domestic church sermon, having relieved it from extreme measures of the baroque literature. The contribution to formation homiletics as sciences in the Kiev theological academy in XIX - beginning ХХ centuries of professors Jacob Amfiteatrov, archpriest Nazarij Favorov and Vasily Pevnitsky is considered. Process of transformation of a view on the nature and the sermon form in the Kiev theological tradition is shown. Influence of the academic theological science on practice of the church sermon during the specified period is disclosed.